Assessment and Mitigation of Information Security Policy in Budgeting System using KAMI Index 4.1 - Tawar; Imam Riadi; Adiniah Gustika Pratiwi; Ariqah Adliana Siregar (Journal of Novel Engineering Science and Technology, 2022)
This Threats to information resources require information security management policies in every agency. The Information Security Index (KAMI Index) is one of the methods developed by the Ministry of Communication and Information Technology, used to evaluate the maturity level, completeness of ISO/IEC 27001:2013 implementation and information security readyness. As a national zakat institution, XYZ Organization has utilized information technology in several systems, including the budgeting system. However, the information security index has never been measured. This condition may result in the risk of threats to information security, so it is necessary to measure. The Budgeting System needs to be measured using KAMI Index 4.1. The assessment criteria are carried out on seven categories to know how the quality of the information security policy is. The results of this assessment, XYZ organization gets an electronic system score is 17, governance 75, risk management 30, framework 31, asset management 37, ICT 38, securing third party involvement 40%, service security 20%, personal data protection 27% so the total score of 5 categories is 211 or at level I+ to II. This organization has started implement the framework at early stage and has not met the initial requirements for ISO/IEC 27001:2013 certification.